2016
DOI: 10.1101/gr.208041.116
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic landscape of fission yeast meiosis alternative-splice isoforms

Abstract: Alternative splicing increases the diversity of transcriptomes and proteomes in metazoans. The extent to which alternative splicing is active and functional in unicellular organisms is less understood. Here, we exploit a single-molecule long-read sequencing technique and develop an open-source software program called SpliceHunter to characterize the transcriptome in the meiosis of fission yeast. We reveal 14,353 alternative splicing events in 17,669 novel isoforms at different stages of meiosis, including anti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 37 publications
5
31
0
Order By: Relevance
“…Comparison of our nRNA LRS and published mRNA LRS data showed a decrease of partially spliced transcripts to 43% from nRNA to mRNA (Supplemental Fig. S5C), indicating that a substantial fraction of partially spliced transcripts will be stable, polyadenylated, cytoplasmic mRNAs that likely represent alternative mRNA isoforms in S. pombe (Kuang et al 2017). In conclusion, LRS of nascent transcripts provides a snapshot of splicing states for multi-B A Figure 3.…”
Section: Full-length Nascent Rna Sequencing Of Multi-intron Transcriptssupporting
confidence: 55%
See 3 more Smart Citations
“…Comparison of our nRNA LRS and published mRNA LRS data showed a decrease of partially spliced transcripts to 43% from nRNA to mRNA (Supplemental Fig. S5C), indicating that a substantial fraction of partially spliced transcripts will be stable, polyadenylated, cytoplasmic mRNAs that likely represent alternative mRNA isoforms in S. pombe (Kuang et al 2017). In conclusion, LRS of nascent transcripts provides a snapshot of splicing states for multi-B A Figure 3.…”
Section: Full-length Nascent Rna Sequencing Of Multi-intron Transcriptssupporting
confidence: 55%
“…Analysis of splicing frequency on a per intron basis from nascent RNA-seq showed that most S. pombe introns are spliced cotranscriptionally (median 0.59), which is lower than in S. cerevisiae (median 0.74), Drosophila, or human cells (Brugiolo et al 2013). Notably, 5% of mRNAs contain introns; recent studies suggest that translation of retained introns contributes to protein diversity in S. pombe (Duncan and Mata 2014;Kuang et al 2017). Intron length is often associated with reduced cotranscriptional splicing (Brugiolo et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is likely that the other identified driving wtf genes also act via a similar mechanism. Two transcripts are common amongst wtf genes and the other three bona fide wtf drive genes also contain a potential alternative translational start site near the beginning of exon 2 (Hu et al, 2017;Kuang, Boeke, & Canzar, 2016;Nuckolls et al, 2017). In addition, Hu et al (2017) found that deletions of the regions upstream of exon 1 of cw9 and cw27 generated poison-only separation of function alleles.…”
Section: Molecular Mechanisms Of Wtf Driversmentioning
confidence: 99%